امكانية تطوير مهنة المراجعة الخارجية في الجزائر على ضوء االتجاهات الدولية الحديثة للمهنة - محمد الأمين لولو; هشام مسمولي (My University, 2024)
The study examined the integration between the reforms undertaken by the Algerian authorities in the auditing profession and the process of adopting international standards. The study examined the content of Law 10-01 on the accounting profession and the content of Algerian auditing standards, while proposing the adoption of international standards to contribute to improving the quality of auditing services and raising the level of professional performance. The study concludes by emphasizing the possibility of adopting international standards for external auditing in Algeria, given their advantages, their non-conflict with local legal requirements, and their compatibility with current Algerian standards. تهدف هذه الدراسة إلىالتكامل بين الإصلاحات التي أجرتها السلطات الجزائرية في مهنة مراجعة الحسابات وعملية تبني المعايير الدولية. وتطرقت إلى مضمون القانون 10-01 المتعلق بالمهن المحاسبية ومحتوى المعايير الجزائرية للمراجعة، مع اقتراح تبني المعايير الدولية للمساهمة في تحسين جودة خدمات المراجعة ورفع مستوى الأداء المهني.. وصلت الدراسة في الأخير إلى مجموعة من النتائج أهمها تبني المعايير الدولية للمراجعة الخارجية للحسابات في الجزائر، نظراً لمزاياها وعدم تعارضها مع المقتضيات القانونية المحلية وتطابقها مع المعايير الجزائرية الحالية. L'étude a examiné l'intégration entre les réformes entreprises par les autorités algériennes dans la profession d'audit et le processus d'adoption des normes internationales. L'étude a examiné le contenu de la loi 10-01 relative à la profession comptable et le contenu des normes algériennes d'audit, tout en proposant l'adoption de normes internationales pour contribuer à l'amélioration de la qualité des services d'audit et à l'élévation du niveau de performance professionnelle. L'étude conclut en soulignant la possibilité d'adopter des normes internationales pour l'audit externe en Algérie, compte tenu de leurs avantages, de leur non-conflit avec les exigences légales locales et de leur compatibilité avec les normes algériennes en vigueur.
Keywords: Keywords : External Audit; Reforms; International Standards of Auditing; Algerian Standards of Auditing; الكلمات المفتاحية: المراجعة الخارجية،، المعايير الدولية للمراجعة، المعايير الجزائرية للمراجعة.; Mots clés : Audit externe; Réformes; Normes internationales d'audit; Normes algériennes d'audit.